The Development of Students’ Worksheets Using The Context of Bangka Belitung Local Cuisine - Setiawan, Tasya; Wafiqoh, Risnina; Vebrian, Rajab (Pelangi (e-Journal), 2024)
This study was conducted to determine the characteristics of LKPD using the context of Bangka Belitung’s local cuisine on a valid and practical system of linear equation in three variables, and to determine the potential effects in training mathematical literacy skills. This study uses the Development (R&D) method with the ADDIE model by Branch. The subjects of the study were the students of class X DKV1 which were divided into a group of 3 students in one-to-one stage, 6 students in small group, a group of 17 students in field test; while there were 20 students as implementation subjects of class X DKV2. The data analysis techniques are the descriptive qualitative and descriptive quantitative. This study developed a very valid LKPD on the material criteria with a percentage of 87%, 88.6% in media criteria, and 75% valid in the language category. The developed LKPD is also very practical with a percentage of 82.4%, and this LKPD has characteristics in accordance with mathematical literacy, contains the context of Bangka Belitung’s local cuisine and contains the system of linear equation in three variables. The potential effect of LKPD in training students' mathematical literacy skills is 56.00% with a Fairly High category.